Effects of filler contacts and interface thermal resistance on the thermal conductivity of heterogeneous spherical filler composites - Yuanyuan Zhang; Xiaojian Wang; Honghong Li; Xinru Fu; Simin Huang; Hao Zhou (eXPRESS Polymer Letters)
Adding heterogeneous fillers with high thermal conductivity (TC) to polymer has been recognized as an effective way to increase the effective thermal conductivity (ETC) of polymer composites. Extensive researches have been conducted on the ETC of composites with heterogeneous fillers. However, the heat transfer enhancement mechanism of heterogeneous fillers remains unknown, and the combined effects of filler size, filler contact, interface thermal resistance (Rc) and other parameters on the ETC have not been explored. In this study, above combined effects are investigated. The results show that the filler contact and Rc are the key factors determining the ETC. The ETC of composite with filler contacts reaches 2.35 at filler content of 25%, which is 11.9% higher than that without filler contacts. The ETC also strongly depends on the R*c (dimensionless form of Rc) ratio (R*c1/R*c2) between two fillers, with it becoming asymmetrical when the amount of R*c(R*c1 + R*c2) is larger. The ETCs decrease with the increase of R*c1/R*c2 when the R*c1/R*c2<1, while they increase with R*c1/R*c2 when the R*c1/R*c2>1. When R*c1 + R*c2 is a constant, the ETC increases with the competing effects of R*c. The models with filler contacts exhibit higher accuracy than other classical models in calculating the ETC across the entire range of filler content.